HUBUNGAN ANTARA DAYA DUKUNG SARANA DAN PENGELOLAAN KELAS DENGAN HASIL BELAJAR SISWA - Mohamad Dudi Solahuddin (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2016)
The study is focused to determine the relationship between school facility (X1), classroom management (X2) and student learning outcomes (Y) in social studies in Bekasi, Subang and Cirebon regencies. The method used is descriptive statistical analysis and path analysis (path analysis). Sample of the study are teachers from 21 schools out of 52 SMPN in Bekasi, teachers from 21 school out of t 60 SMPN in Subang, and teachers 18 schools out of 59 SMPN 59 in Cirebon. The results show that (1) school facility correlated significantly with classroom management amounted to 0.381. (2) The results of school facility and management classes do not correlate significantly with student competency test. (3) school facility affects classroom management significantly with significance value of 0.003. (4) Variable school facility and the management class do not affect the test results of student competence significantly. Based on the results of the study, it is recommended that further study is extremely of importance to conduct to obtain other factors that influence student learning outcomes. For example, intelligence, motivation, interests, health, learning strategies, media and competence of teachers themselves. Dinas Pendidikan is urged to provide and improve guidance to the teachers and provide sufficient funding to improve the quality of school facility. To improve teachers’ competence, it is also recommended that LPMP Jawa Barat provides assistance and guidance.